The spliceosome recycling factor, SART3, regulates H2B deubiquitination by Usp15 - Long, Lindsey J., author; Yao, Tingting, advisor; DeLuca, Jennifer, committee member; Luger, Karolin, committee member; Wilusz, Jeffrey, committee member (Colorado State University. Libraries, 2014)
In eukaryotes plasticity of chromatin architecture is paramount to allow proper regulation of processes such as transcription regulation, DNA repair, and DNA replication. Modulation of chromatin dynamics is primarily achieved via signaling to chromatin modifiers and remodelers though a complex code of histone post-translational modifications (PTMs). These PTMs include methylation, acetylation, phosphorylation, and ubiquitination. In comparison to other histone PTMs, attachment of the 8.5 kDa ubiquitin (Ub) protein stands out due to its considerable size. The majority of histone monoubiquitination occurs on histones H2A and H2B (at lysine residues 119 and 120, respectively), and these modifications have roles in the regulation of many cellular processes including transcription, pre-mRNA processing, and DNA damage repair. To uncover the mechanisms underlying various functions associated with ubiquitinated histones, we generated non-hydrolyzable Ub-histone mimics and assembled them into H2A/H2B dimers or nucleosomes. Quantitative mass spectrometry was employed to identify proteins that bound to unmodified or modified histone dimers and mononucleosomes. We also found that, within the context of a mononucleosome, Ub, when attached to H2B, partially obscures the H2A/H2B acidic patch. Among the proteins that were identified, a deubiquitinating enzyme (DUB), Usp15, exhibited high affinity and specificity towards ubiquitinated histone dimers. Further characterization demonstrated that Usp15 is a bona fide histone DUB and preferentially deubiquitinates Ub-containing histone octamers versus Ub-containing mononucleosomes. Usp15 associates with the U4/U6 spliceosome recycling factor, SART3, which we found also bound to histones. These interactions result in more efficient histone deubiquitination by Usp15. In cells, depletion of SART3 results in elevated ubH2B levels that we show is due to a decreased rate in H2B deubiquitination. These observations indicate SART3 may play a role in regulating ubH2B dynamics as a possible mechanism by which regulate alternative splicing and transcription. Depletion of SART3 also alters transcriptional and alternative splicing patterns. By chromatin immunoprecipitation, we confirmed that SART3 localizes to at least a subset of genes whose transcription decreased upon SART3 depletion. Future studies will be designed to elucidate the mechanism by which Usp15, SART3, and ubH2B work together to regulate transcription and alternative splicing.
Keywords: histone modification; ubiquitin; ubH2B; deubiquitination; histone chaperone; RNA splicing